Bridging past and present: integration of modern stormwater infrastructure into a historic interpretation site - Holliday, Devin (My University, 2025)
How can modern stormwater management practices be integrated into a historical preservation site like the Marlatt Homestead, ensuring both ecological health and the preservation of cultural heritage, while also creating opportunities for public education on sustainable water management? This research investigates the intricate balance between watershed management and the preservation of historical homesteads, a challenge that sits at the intersection of environmental sustainability and cultural heritage. Watershed management involves practices designed to protect and manage water resources, which can sometimes conflict with the preservation of historical structures that contribute to a site’s cultural value. This study aims to explore how landscape architecture can reconcile these competing interests through a multidisciplinary approach. By reviewing literature on both historical preservation and watershed management, conducting field assessments, and analyzing case studies, the research will identify best practices for integrating modern environmental strategies with the conservation of historical sites. Key areas of focus include evaluating the environmental impacts of preserving historical features, navigating regulatory challenges, and engaging with community stakeholders. The research will also explore innovative design solutions and adaptive reuse strategies that respect historical integrity while addressing contemporary environmental needs. Ultimately, this study seeks to develop practical recommendations for landscape architects and policymakers to create designs that harmonize ecological health with cultural preservation, ensuring sustainable and culturally sensitive land use.
Keywords: Stormwater; Green infrastructure; Historic preservation; Marlatt homestead